2018
DOI: 10.1123/japa.2016-0368
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Dementia in Nursing Homes: Views of Staff and Family Carers

Abstract: This paper reports the qualitative component of a randomized controlled trial which evaluated the impact and feasibility of a physical exercise intervention on individuals living with dementia in nursing homes. Interviews were conducted with 10 staff and nine family carers about their views and opinions of physical exercise (n = 19). Thematic content analysis revealed both benefits and barriers to physical exercise for individuals living with dementia in nursing homes. Another theme was the influences of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The physical, cognitive, behavioural, and social benefits reported in this study are similar to those reported in a recently published analysis of the perceptions of staff and family carers of RACF residents participating in a physiotherapist-led exercise programme (Brett et al., 2018). In contrast to this study, we did not receive reports of increased levels of agitation, or antisocial behaviour towards care staff, and this is an avenue for further exploration.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The physical, cognitive, behavioural, and social benefits reported in this study are similar to those reported in a recently published analysis of the perceptions of staff and family carers of RACF residents participating in a physiotherapist-led exercise programme (Brett et al., 2018). In contrast to this study, we did not receive reports of increased levels of agitation, or antisocial behaviour towards care staff, and this is an avenue for further exploration.…”
Section: Discussionsupporting
confidence: 86%
“…In recognising time as a major barrier, care staff almost unanimously agreed that this type of programme should be delivered by trained staff, such as EPs. This notion is similar to the findings of Brett et al. (2018) study, whereby interviewees suggested exercise interventions be run by a person ‘dedicated’ to the role.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The inclusion of the wishes, needs, attitudes, and beliefs of people living with dementia concerning physical activity is a crucial prerequisite for the development of targeted and successful interventions in the long-term care setting ( de Souto Barreto et al, 2016 ). These aspects have not been discussed in physical activity research so far, and no significant efforts have been made to consider the voices of people living with dementia in care homes concerning the development of exercise programs ( Brett et al, 2018 ; Tak et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sparse data we identified relating to the ethnic diversity of participants in Australian dementia research suggest that CALD people are under‐represented. We searched the Scopus database and of the 15 published dementia clinical trials published between 2016 and 2018, two studies reported that 33.3% and 31.6% of participants were from non‐Australian backgrounds, and three studies reported that 7.1%, 12.5% and 57.0% of participants spoke English as a second language . The remaining ten studies did not report ethnicity‐related data.…”
mentioning
confidence: 99%